β2 Integrins As Regulators of Dendritic Cell, Monocyte, and Macrophage Function - Schittenhelm, Leonie; Hilkens, Catharien M.; Morrison, Vicky L. (Frontiers in Immunology, 2017)
Emerging evidence suggests that the β2 integrin family of adhesion molecules have an important role in suppressing immune activation and inflammation. β2 integrins are important adhesion and signaling molecules that are exclusively expressed on leukocytes. The four β2 integrins (CD11a, CD11b, CD11c, and CD11d paired with the β2 chain CD18) play important roles in regulating three key aspects of immune cell function: recruitment to sites of inflammation; cell–cell contact formation; and downstream effects on cellular signaling. Through these three processes, β2 integrins both contribute to and regulate immune responses. This review explores the pro- and anti-inflammatory effects of β2 integrins in monocytes, macrophages, and dendritic cells and how they influence the outcome of immune responses. We furthermore discuss how imbalances in β2 integrin function can have far-reaching effects on mounting appropriate immune responses, potentially influencing the development and progression of autoimmune and inflammatory diseases. Therapeutic targeting of β2 integrins, therefore, holds enormous potential in exploring treatment options for a variety of inflammatory conditions.